PENGARUH SISTEM PENGENDALIAN INTERNAL PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Oganisasi Perangkat Daerah Kabupaten Rokan Hilir) - Novitasari Lia Elita Eva; Nasrizal Nasrizal; Natariasari Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The sample in this study was determined by using purposive sampling method intotal there are 27 OPD in Rokan Hilir Regency. The analytical method used in thisresearch is multiple regression analysis using SPSS v22.The purpose of this study was totest the competence effect of Of The Government Internal Control System, The HumanResources Competencies, The Utilization Of Information Technology And TheApplication Of Regional Financial Accounting System To The Quality Of LocalGovernment Financial Report. Respondents in this study is the structural officialsinvolved in drafting the budget. The results showed that: 1) Effect of The GovernmentInternal Control System affect the quality of financial reports with significant value0,015 <0,05. 2) The Human Resources Competencies significantly influence the quality offinancial reports with significant value 0,004 <0.05. 3) the utilization of InformationTechnology significantly influence the quality of financial reports with significant value0,000 <0.05 .4) The Application Of Regional Financial Accounting System a significanteffect on the quality of financial reports with significant value 0.000 <0.05.Keyword : quality of financial reporting, governmet internal control system, humanresources competency, technology information, regional financialaccounting system